Efektivitas Pelaksanaan Pelatihan Dasar (LATSAR) CPNS Golongan III Angkatan III Berbasis e-Learning di Kabupaten Tanjung Jabung Barat - Musfarita Affiani (Universitas Batanghari Jambi, 2020)
The outbreak of the corona virus (covid-19) in Indonesia which continued to increase until early March 2020. This research focused on the effectiveness of online-based learning applications that are applied due to physical distancing policies. Physical distancing was applied by the Indonesian government as a preventive for the transmission of the COVID 19 virus, but it was not very successful because positive numbers continue to grow. Through this research, the researcher wants to analyze how effective the implementation of the learning system is from the training participant perspective. The sample of this study was 39 training participant Group III Batch III at Tanjung Jabung Barat. The instrument used was a questionnaire distributed online using the google form link. Based on the data obtained, shows that the implementation of online learning has been carried out effectively seen from the readiness of the facilitator, the ability to use applications, responses and benefits obtained.